Hand hygiene quality indicator in Nursing home Ljubljana Slovenia - Medjedovic, Sabina; Kovacic, Martina Dimnik; Toroman, Dragana (Polish Journal of Public Health, 2026)
Introduction. Hand hygiene is a key indicator of quality and safety in long-term care facilities. This study aimed to assesscompliance with hand hygiene practices in a nursing care home for older adults in 2025.Methods. An observational audit was conducted from 1 July to 27 August 2025 across six departments of the care home, followingthe World Health Organization (WHO) “Five Moments for Hand Hygiene” methodology. Observations were performedopenly, and healthcare personnel were aware that hand hygiene monitoring was taking place. The minimum required numberof 424 hand hygiene opportunities was defi ned according to institutional standards issued by the Ministry of Health. The targetnumber was not based on a statistical power calculation but followed predefi ned quality assurance requirements.Results. Overall hand hygiene compliance was 84.76%, with the highest adherence among physiotherapists, occupationaltherapists, and social workers (100%), followed by healthcare professionals with compliance above 80%, and the lowest amongcleaning staff (68.75%). A total of 433 hand hygiene opportunities were observed. Overall compliance ratio was 367 out of 433(84.76%), with a 95% Wilson confi dence interval of 81.07% to 87.84%.Discussion. The results indicate good overall compliance with hand hygiene practices, although improvements are possible regardingdisinfectant accessibility and the regularity of monitoring. These fi ndings may inform quality improvement efforts aimedat strengthening resident safety and care quality.